Tinjauan Hukum Pidana Terhadap Kejahatan Kesusilaan Yang Dilakukan Oleh Anggota Dewan Perwakilan Rakyat Daerah (Studi Kasus Di Pengadilan Negeri Soe) - Selan, Nadia Melisa; Fallo, Debby F. Ng; Wilhelmus, Bhisa Vitus (Artemis Law Journal, 2025)
This study analyzes the main legal issues in the Soe District Court Decision No. 38/Pid. B/2021 relating to the application of Article 281 paragraph (2) of the Criminal Code (maximum sentence of 2 years and 8 months) for crimes against morality committed by members of the DPRD, while the alternative charge of Article 289 of the Criminal Code (sentence of 9 years) was not applied without adequate legal explanation. This study shows that the defendant has been proven to have committed repeated non-penetrative sexual harassment in front of witnesses, with the victim suffering from Post-Traumatic Stress Disorder (PTSD) based on the results of a psychological examination. The 8-month sentence imposed is considered disproportionate to the impact of the trauma experienced by the victim, the frequency of the act, the perpetrator's position as a public official, and a similar verdict handed down at the Yogyakarta District Court which reached 1.5 years. Fundamental criticisms include the use of the mitigating factor of "family backbone" which can strengthen patriarchal views, as well as the need for an assessment of consistency in sentencing and the application of a restorative approach in cases of sexual violence based on power relations.